Pregnancy: A window of opportunity for refining and mitigating the fetal origins of adult health and disease, and maternal cardiovascular futures - Joewono, Hermanto T (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Maternal nutrition, mental health, and environmental factors during pregnancy significantly influence the long-term physical and mental health of offspring, supporting the concept of Fetal Origins of Adult Disease (FOAD) and Developmental Origins of Health and Disease (DOHaD). Adverse pregnancy outcomes like preeclampsia and gestational diabetes increase the mother's future risk of cardiovascular disease, highlighting the need for broader maternal health strategies beyond childbirth.   ABSTRACT This review explores the profound impact of pregnancy on fetal development and long-term maternal cardiovascular health, emphasizing how early-life conditions shape lifelong health. The concept of Fetal Origins of Adult Disease (FOAD) or Developmental Origins of Health and Disease (DOHaD) is discussed, highlighting how maternal nutrition and environmental factors during pregnancy predispose offspring to chronic diseases later in life. Maternal mental health is also explored, with depression and anxiety during pregnancy linked to lasting effects on offspring, including increased risks of mental health disorders and chronic conditions in adulthood. The study "Like Mother, Like Daughter" is examined to illustrate intergenerational risks such as preeclampsia and intrauterine growth restriction (IUGR), emphasizing the role of maternal health. Additionally, the long-term cardiovascular consequences of adverse pregnancy outcomes—such as preeclampsia, gestational diabetes, and preterm birth—are discussed, noting that they elevate the mother's risk of cardiovascular disease (CVD) in later life. The rising prevalence of obesity during pregnancy further exacerbates these risks. The paper calls for a shift in obstetrics from a narrow focus on pregnancy management to a broader approach that addresses both maternal and fetal health for long-term benefits. By recognizing pregnancy as a critical window to influence future health, comprehensive strategies could help mitigate chronic diseases in both mothers and children